Abu Dhabi International Petroleum Exhibition and Conference 2008
DOI: 10.2118/118434-ms
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Interwell Water Saturation in Pattern Flood Pilots in a Giant Gulf Oil field

Abstract: Peripheral water flooding has been the preferred pressure maintenance tool for many gulf carbonate reservoirs over the past 30 years. Due to uneven sweep and pressure distribution, this technique has given way to pattern floods in several gulf fields. As these new floods are established, it is important to understand the water saturation between wells to properly manage the sweep and recovery. In 2007, ADCO initiated water injection (WI) and WAG pilots to test the recovery strategy. The pilot employs advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Crosswell resistivity mapping has been used to monitor water injection in several geologic settings, including in a diatomite reservoir in California (Wilt et al, 2005) and in carbonate fields in the Middle East (Bhatti et al, 2008;Marsala et al, 2008). An example from Oman (Mieles et al, 2009) is shown in Figure 10.…”
Section: Electromagnetic Monitoringmentioning
confidence: 99%
“…Crosswell resistivity mapping has been used to monitor water injection in several geologic settings, including in a diatomite reservoir in California (Wilt et al, 2005) and in carbonate fields in the Middle East (Bhatti et al, 2008;Marsala et al, 2008). An example from Oman (Mieles et al, 2009) is shown in Figure 10.…”
Section: Electromagnetic Monitoringmentioning
confidence: 99%
“…Time-lapse crosswell electromagnetic has been applied for tracking interwell fluid movement (Hoversten et al, 2001;Wilt and Alumbaugh, 2001;Bhatti et al, 2008). Time-lapse controlled-source electromagnetic (CSEM) has also been explored for reservoir monitoring applications (Lien and Mannseth, 2008;Orange et al, 2009;Black et al, 2010;Shahin et al, 2010;Berre et al, 2011;Liang et al, 2011b;Andreis and MacGregor, 2011).…”
Section: Introductionmentioning
confidence: 99%